Nutritional Information and Characteristics Required by Adolescents and Mothers in Developing Health Applications "MoGiz" - Miyanto, Dwi; Yuliati, Endri; Prasetyaningrum, Yunita Indah (jitek, 2022)
Mobile applications about health have been widely developed but not yet effective as well as suit to user needs. It is because the design process does not involve potential users or user-centered design (UCD). This study aims to obtain information about the needs of groups of adolescents and mothers of children under five on the health application namely MoGiz (Monitoring Gizi). The method uses a qualitative approach through Focus Group Discussion with 6 and 9 informants from group of youths and mothers, respectively. Data analysis was carried out by interpreting the results of a series of transcripts, coding, and arranging the topics and themes found. The results show that teenagers want applications about adolescent health, while mothers of toddlers want applications about toddler health. Both groups expect applications to be small, attractive, containing articles and videos. In conclusion, it is recommended that the application contains health information according to the characteristics of the needs of potential users.